Can we change a genetically determined future?. (15th May 2015) - Fernandes, Lígia Rodrigues; Rodrigues, Luis Vaz; Costa, Filipa; Martins, Yvette
Abstract : We describe the clinical evolution of the first patient diagnosed with a severe α-1 antitrypsin (AAT) deficiency caused by a rare null allele (Q0Ourém), over the past 18 years. We highlight the clinical course of the disease as well as the evolution of the pulmonary function tests from initial diagnosis and the benefits of augmentation therapy for this specific condition. We report the case of a 43-year-old man with exertion dyspnoea who was observed in our pulmonology unit. The unexpected findings in the complementary examinations led us to diagnose AAT deficiency and to the discovery of a new mutation with the SERPIN A1 gene (hence named Q0Ourém) responsible for the disease. Augmentation therapy was initiated, as is the protocol in this condition. Eighteen years after the diagnosis, the patient is clinically stable, fully autonomous and maintaining an acceptable quality of life, despite severe obstructive lung disease.